An up-converting phosphor technology-based lateral flow assay for point-of-collection detection of morphine and methamphetamine in saliva. Issue 19 (31st August 2018) - Hu, Qiushi; Wei, Qiaozhen; Zhang, Pingping; Li, Shuang; Xue, Lei; Yang, Ruifu; Wang, Chengbin; Zhou, Lei
Abstract : Rapid and quantitative detection of morphine and methamphetamine in saliva with high sensitivity and accuracy by an UPT-LFA. Abstract : Morphine (Mop) and methamphetamine (Met) are highly addictive drugs worldwide. Point-of-collection testing (POCT) for drug-of-abuse screening is important in abuse/rehabilitation clinics and law-enforcement agencies. We established an up-converting phosphor technology-based lateral flow assay (UPT-LFA) as a point-of-collection testing (POCT) method, namely Mop-UPT-LFA and Met-UPT-LFA, for the detection of morphine and methamphetamine without complicated sample pre-treatment, respectively, in saliva. The sensitivities of the Mop-UPT-LFA and the Met-UPT-LFA were 5 and 10 ng mL −1 with accurate quantitation of 5–100 ng mL −1 and 10–250 ng mL −1 for morphine and methamphetamine, respectively, for a detection time of 15 min. In reference to the detection limits of 20 and 25 ng mL −1 for morphine and methamphetamine, respectively, in the Driving Under the Influence of Drugs, Alcohol and Medicines (DRUID) program of the European Union, the percentage test/control (T/C) ratio of the UPT-LFA between 2 and 15 min reached 101% and 86%, and the UPT-LFA produced accurate qualitative results in 2 min for 100 simulated-saliva samples with the exception of a few weakly positive samples. The sample and sample treating buffer were mixed and added to the test strip, and the test was conducted 15 min later. Although we found no significant difference between the UPT-LFA quantitative test and the liquid chromatography tandem mass spectrometry (LC-MS) test, compared with the latter, the UPT-LFA was substantially faster and had higher detection efficiency. The UPT-LFA showed more accurate qualitative results than the LC-MS for 50 simulated-saliva samples. The ease of operation, high sensitivity, and accuracy of the UPT-LFA make it a valid candidate POCT method for drug-of-abuse screening.